Post CAR T-cell therapy outcomes and management in HSCT-naive patients: a single-center experience - Phillips, Christine L.; Krupski, Christa; Khoury, Ruby; Dandoy, Christopher E.; Nelson, Adam S.; Galletta, Thomas J.; Faulhaber, Angela; Davies, Stella M.; Rubinstein, Jeremy D. (Frontiers in Hematology, 2023)
Background Tisagenlecleucel (tisa-cel) is increasingly being used in hematopoietic stem cell transplantation (HSCT)-naive patients. Outcomes for HSCT patients following chimeric antigen receptor (CAR) T-cell therapy demonstrate low relapse rates; however, a significant number of patients who receive tisa-cel can maintain remission without an HSCT. Multiple factors are considered when choosing whether or not to proceed with HSCT. Methods We retrospectively reviewed 31 patients who had received tisa-cel at our institution and who were transplant naive at the time of infusion. The aim was to determine the rate and timing of consolidative HSCT, factors that led to HSCT, and overall survival. Results Three of the 31 patients were non-responders to tisa-cel and ultimately died of disease. Twelve of the 28 responders remain alive with no evidence of disease (NED) without subsequent therapy. Of these patients, 5 of the 12 had isolated extramedullary acute lymphoblastic leukemia (ALL) (CNS, n = 4; testes, n = 1) and 2 of the 12 had Down syndrome, so no transplantation was planned. In the remaining 5 of 12 patients, close monitoring for signs of relapsed ALL, using serial next-generation sequencing (NGS) minimal residual disease (MRD) and lymphocyte subpopulation measurements, was performed. Owing to continued negative findings, no HSCT was chosen. Ultimately, 43% (12 of 28) of responders proceeded to HSCT, with three receiving tisa-cel as a planned bridge to HSCT as a result of CD22 negativity and/or provider preference (two patients survived with NED); three proceeded to HSCT as a result of early loss of B-cell aplasia (BCA) (all survived with NED); and six had salvage HSCT following relapse (three patients survived with NED and one patient was alive in relapse). Three of the 28 patients died following relapse post CAR T-cell therapy without HSCT. The final patient had an isolated extramedullary soft tissue CD19+ relapse 1 year post tisa-cel treatment, and is now NED without HSCT and persistent BCA. Conclusion Close monitoring of NGS results and BCA, as well as consideration of the site of the disease, can spare a subset of patients HSCT with the maintenance of leukemia-free remission, while still allowing for later HSCT in others. In our cohort, only a small subset of patients was unable to proceed to HSCT following relapse post-CAR T-cell therapy.